Clinical outcomes of proximal gastrectomy with gastric tubular reconstruction and total gastrectomy for proximal gastric cancer: A matched cohort study - Fu, Jingxiao; Li, Yi; Liu, Xuechao; Jiao, Xuelong; Wang, Yuhao; Qu, Hongyu; Niu, Zhaojian (Frontiers in Surgery, 2023)
Background Proximal gastrectomy with gastric tubular reconstruction is a surgical procedure that can preserve function in patients with proximal gastric cancer. However, whether gastric tubular reconstruction with proximal gastrectomy has certain advantage in some aspects over total gastrectomy is controversial. To evaluate the benefit of gastric tubular reconstruction after proximal gastrectomy, we compared gastric tubular reconstruction with total gastrectomy for proximal gastric cancer. Methods A total of 351 patients were enrolled. Concurrent total gastrectomy patients matched with the Proximal gastrectomy group in age, sex, body mass index, clinical stage, and ASA score were selected by propensity score matching. Preoperative basic information, perioperative indicators, histopathological features, postoperative complications and nutritional status, reflux were compared between the two groups. Results There was no significant difference in the incidence of reflux between two groups (14.8% and 6.5% respectively, P=0.085). There were significant differences between the two groups in bowel function recovery (2.29±1.16 vs 3.01±1.22; P =0.039) and start of soft diet (4.06±1.81 vs 4.76±1.69; P =0.047). There were no significant differences between the two groups in nutritional status one year after surgery. However, the decrease in serum hemoglobin in the TG group at 3 and 6 months after surgery was significantly higher than that in the PG group (P = 0.032 and 0.046, respectively). One month after surgery, %BW loss in TG group was significantly lower than that in the PG group (P =0.024). Conclusions The Proximal gastrectomy group has better clinical outcome and gastric tubular reconstruction is simple, similar complications and reflux rates, gastric tubular reconstruction may be more suitable for proximal gastric cancer. Keywords Proximal gastrectomy; Gastric tubular reconstruction; Reflux esophagitis; Nutritional status; Hemoglobin